Arbor City Community Foundation - Schmedders, Karl; Walker, Russell, 1972-; Stritch, Michael ([London] : SAGE, 2016)
The Arbor City Community Foundation (ACCF) was a medium-sized endowment established in Illinois in the late 1970s through the hard work of several local families. The vision of the ACCF was to be a comprehensive centre for philanthropy in the greater Arbor City region. This study examines the strategies and returns of the ACCF.
Originally Published in: Schmedders, K., Walker, R., & Stritch, M. (2011). Arbor City Community Foundation (Executive Education Version). 5-310-503. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Nonprofit organizations -- Finance -- Case studies; Risk management -- Case studies; Community foundations -- Illinois -- Case studies